Pump handbook (New York : McGraw-Hill, 1986)
This book is about: Classification and Selection of Pumps; Centrifugal Pumps; Displacement Pumps; Jet Pumps; materials of Construction; Pumb Drivers; Pump Controls and Valves; Pumping Systems; Pumps Services...
Keywords: Pumping machinery; Pumping machinery -- Handbooks, manuals, etc